ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CARBON EMISSION DISCLOSURE PADA PERUSAHAAN DI INDONESIA (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2010-2012) - Richatul Jannah; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study aimed to obtain empirical evidence about the influence of Media Exposure, type of industry, profitability, company’s size, environmental performance, company’s Leverage to the extent of emission carbon disclosure in Indonesia companies. To measure the extent of carbon emission disclosure used checklist that was developed based on the information request sheets provided by the carbon disclosure project (CDP). The population of this study was all companies listed in Indonesia Stock Exchange (ISX) in 2010-2012. Sample of this study was non financial companies listed in Indonesia Stock Exchange (ISX) in 2010-2012 used purposive sampling method. There were 35 companies in 2010, 37 companies in 2011, 37 companies in 2012 which fulfilled criterion as the research sample. The classical assumpstion was used for data analysis and regression analysis for testing hypothesis. The results of this study showed that Media Exposure, type of industry, profitability, firm size, and companies’ Leverage significantly influence to the extent of carbon emission disclosure. Meanwhile environmental performance had no significantly influence to to the extent of carbon emission disclosure.